2017
DOI: 10.21474/ijar01/3321
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Tirads [Thyroid Imaging Reporting and Data System] and Histopathological Findings in Evaluation of Thyroid Nodules.

Abstract: Purpose: Ultrasound [US] is an excellent noninvasive modality to evaluate thyroid nodules.Aim of our study was to characterize the thyroid nodules according to grey scale sonographic features into high suspicious ,probably benign, benign aspects and normal thyroid using TIRADS scoring system and to characterize the thyroid nodule according to the sonographic features into a specific TIRADS stage and correlate the results with the histopathological examination findings wherever possible. Material And Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Extra-thyroid extension (ETE) is considered in several risk systems for thyroid cancer, including ours (ACR-TIRADS US lexicon), because it is a critical predictor of clinical outcomes in differentiated thyroid cancer (DTC) patients. (23) In the present study, we found 16 nodules with extra-thyroid extension, and all of them revealed malignancy by pathology, confirming what other studies reported Azab et al (21) , Mohanty and Mishra (24) and Patil et al (25) where nodules with ETE had 100% malignancy risk.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Extra-thyroid extension (ETE) is considered in several risk systems for thyroid cancer, including ours (ACR-TIRADS US lexicon), because it is a critical predictor of clinical outcomes in differentiated thyroid cancer (DTC) patients. (23) In the present study, we found 16 nodules with extra-thyroid extension, and all of them revealed malignancy by pathology, confirming what other studies reported Azab et al (21) , Mohanty and Mishra (24) and Patil et al (25) where nodules with ETE had 100% malignancy risk.…”
Section: Discussionsupporting
confidence: 91%
“…Very hypoechogenicity, ETE, taller than wide nodules, and PEF had a 100%, 100%, 100%, and 95% risk for malignancy, respectively. Within the same line, Patil et al (25) mentioned that all nodules with marked hypoechogenicity and ETE had a 100% malignancy risk.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, irregular margins as well as taller than wider shapes are also predictors of malignancy albeit with low sensitivity of 31.8% while the speci city, positive and negative predictive values were almost 90%. Comparable ndings were reported by the same study from India (30) who observed that poorly de ned irregular margins had equally low sensitivity but high speci city and positive predictive value. These ndings are also similar to a study reported by Jabar et al that showed, irregular margin and taller than wider appearance had low sensitivity and PPV and high speci city and NPV (31).…”
Section: Discussionsupporting
confidence: 62%
“…Various imaging modalities have been used in diagnosis of thyroid diseases. Thyroid volume can be calculated accurately by ultrasonography [2]. Sonographically, the normal thyroid parenchyma has a homogenous, medium to high level echogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The capsule of the thyroid gland is represented by a thin hyperechoic line around the thyroid lobes. The capsule can become calcified in patients with uremia or in disorders of calcium metabolism [2]. On Sonographic evaluation majority of the thyroid nodules are asymptomatic and are detected incidentally [3][4][5] Ultrasonography followed by USG guided FNAC is usually done in evaluating any thyroid nodule that is palpable on physical examination.…”
Section: Introductionmentioning
confidence: 99%